Related Industry Needs Towards English for Hotel and Tourism Course Learning Material - Kosasih, Fauzy Rahman; Budiman, Rahmat; Warsihna, Jaka; Ramdani, Zulmi (UIN Sunan Gunung Djati Bandung, 2025)
In the field of tourism, English serves as a global language of communication between tour guides and international tourists, as well as in relation to tourist attractions, culture, history, food, beverages, accommodations, transportation, souvenirs, services, and many other aspects. The needs analysis/assessment requires the synchronization of the demand (tourism users) and supply (English for tourism). In the Indonesian context, there has been an increasing market demand from the tourism sector for higher education institutions to provide their best graduates with relevant and aligned skills. This study investigates the industry's needs for English in the context of hotel and tourism courses. The study employs a mixed-methods approach, using both quantitative data from surveys and qualitative data from interviews. The results indicate that ten out of twelve topics in the English for Hotel and Tourism book of the English Education program at Universitas Terbuka are relevant to the respondents' occupations/industries. However, two topics were deemed by most respondents to be irrelevant to their jobs. For improvement, this study recommends that these two irrelevant topics be altered or modified.